Konstruksi Makna Hijab Dalam Film Merindu Cahaya De Amstel Karya Arumi e. - Fadhilah, Chusnul; Malayati, Robi’ah Machtumah (Menara Tebuireng, 2023)
The association of hijab with the identity of Muslim women remains a subject of debate. Women have an important position in Islam. Islam is very concerned about the dignity and dignity of women. One of the social constructions formed by mass media is the social construction of veiled women. The social construction displayed by the mass media regarding veiled women fosters a certain image in society. Film is an audiovisual medium used to convey messages to groups of people congregating in a particular location. The main topic of discussion in this karya is the plot and specific details that are contained in the movie Merindu cahaya de Amstel. Qualitative research methods were used in this study. The purpose of this study is to describe the signs of the meaning of hijab and the structure of the meaning of hijab in the film Merindu Cahaya de Amstel by Arumi E. Maxstream Original and Unlimited Production. Utilized data collection techniques include document analysis and case study research. To answer the formulation of the problem described above, researchers use a qualitative approach using the semiotic analysis model of Charles Sanders Peirce. As a result, researchers found several meanings of hijab in the film Merindu Cahaya de Amstel: (1) The meaning of hijab as an identity Muslim women. (2) Maintain the social behavior of a Muslim woman. (3) Hijab embodying women with noble morals. (4) Exalting a person Muslimah. (5) Hijab as an obligation for Muslim women. Keywords: Construction, Meaning of Hijab, Semiotics.